Disaster Sites Roaming Smart Car with Hand Gesture Controller - Zapiee, Mohd Khuzaimi; Mohana, Dharnishaa; Balasingam, Sheshalani; Panessai, Ismail Yusuf (Lamintang Education and Training Centre, in collaboration with the International Association of Educators, Scientists, Technologists, and Engineers (IA-ESTE), 2022)
This research is about an Internet of Things (IoT) project and research about smart car development. IoT is machine or device that can transfer data over a network without a connection between human-to-human or human-to-device interaction. One of the significant of IoT is the revolution of smart car. This project is a research about smart car that help civilian in distress that have been caught in a natural disaster like land slide or even an earthquake and traps in a collapsed building or it can be a smart car that can recon the site. This smart car can assist the rescue squad to detect that survivor by going through the small hole that been create by the collapsed building and give the rescue squad the where about of the survivor and provide information to the rescuer about the site. The smart car also have solar system to power the system and can run longer than powered only with battery. The smart can also have anti capsize that may make the smart car overturn in the disaster site while roaming in the disaster to detect the victims. This feature help the smart car easily to roam freely with the unstable environment. The smart car also provided with camera for the rescue squad to analyse the structure in the disaster and avoid to dig the rubble or disaster site and killed the victims and the user can gain the insight of the site and gain information more detailed. The smart car can be controlled with a globe type controller for easier the user to control the smart car in the unstable and fragile site.